INFORMATION INTERSECTION IN EARTH SCIENCES - Бахова, Н. (Proceedings of National Aviation University (archive), 2012)
Historically important stages of society information are considered. Features of information forecasts ofthe information civilization progress are analyzed. Fundamental problems of biotical management of anenvironment are illuminated. The task of studying features of informational interaction of the person andbiota is proposed. The possibilities and the difficulties of construction of information models are shown. Thegeophysical environment information model has been proposed